Ahlussunnah Wal Jamaah Creed Education as a Preventer of Bullying Behavior (Case Study at the Darun Najah Balen Islamic Boarding School) - Ahmad Muthi' Uddin; Alaika Abdi Muhammad; Agus Moh. Sholahuddin; M. Ahsanur Rofi' (al-Afkar, Journal For Islamic Studies, 2024)
Aswaja education is one of the subjects included in the madrasa curriculum, especially in Salaf Islamic boarding schools, where in Aswaja learning the values of faith and morals are explained which are very fundamental for students so that they can be applied in everyday life. Meanwhile, the values of ahlussunnah waljama'ah include; tolerance and respect for others is very important to instill in students so that the mindset and attitudes possessed by students can be formed well and away from harsh and easily emotional attitudes. This research analyzes how the Darun Najah Islamic Boarding School instills the values of the ahlussunnah waljamaah faith through ASWAJA learning and other religious activities. This research includes field research by conducting observations and interviews. The results of this research include: 1).Aswaja education has an important role in the development and development of children, especially with regard to instilling religious and social values. This was based on the scholars of the classical period, at that time they placed more emphasis on strengthening Islamic religious teaching which was more focused on moral education, such as tolerance and respect for diversity. 2). Bullying is an act that hurts someone intentionally or with the intention that already exists within the perpetrator which results in being hurt, disturbed and harmed. The background to the existence of the Darun Najah Islamic Boarding School applies Aswaja values due to cases of bullying among Islamic boarding schools. This behavior is caused by 2 factors, namely family factors and individual factors.  From this problem, the Darun Najah Islamic boarding school created a concept to overcome bullying or bullying behavior, including: forming a tolerant character, respecting differences, habituation to manners, friendly habits, and uswah (exemplary) methods.